Impact Of Maternal Hypothyroidism In Women With Gestational Diabetes Mellitus And Its Adverse Pregnancy Outcomes In South-Indian Population- A Prospective Study (Journal of Pharmaceutical Negative Results, 2022)
Introduction: The concurrent influence of Gestational diabetes mellitus (GDM) and hypothyroidism on the incidence of hypothyroidismin GDM is not yet clearly reported. Thyroid dysfunction has been associated with adverse obstetric outcomes. However, less is knownregarding subclinical hypothyroidism and its relationship to pregnancy complications.Methods: This prospective study was conducted with a total of 300 antenatal patients with GDM according to DIPSI criteria after 24weeks and above were subjected to thyroid function tests. Patients with normal FT3, normal FT4 and S.TSH between 3.0mIU/L -10.0mIU/L were diagnosed as Subclinical hypothyroidism and S.TSH more than 10.0mIU/L were diagnosed as Overt hypothyroidism.These patients were followed up and both maternal-fetal outcomes were observed in GDM patients with and without hypothyroidism.Results: In the study, 14% of GDM women developed hypothyroidism, all of which were subclinical. When compared to GDM women,patients with combined endocrinopathy were more prone for Hypertensive Disorders (HD) in pregnancy. Other foetal outcomes, suchas preterm delivery (P= 0.384), RDS (P= 0.465), sepsis (P= 0.366), and jaundice in newborns (P= 0.193), and maternal outcomesincluded anemia (P= 0.720), abruptio placenta (0%), mode of delivery (P= 0.9), and oligohydramnios were not statistically significant.Conclusion: The incidence of hypothyroidism in GDM patients was only 14%. The incidence of HD in Pregnancy was more incombined endocrinopathy (26.19%) compared to GDM (13.57%) (P=0.035). This indicates the increased incidence of HD inPregnancy, which emphasizes the importance of overseeing pregnancy as HD in Pregnancy may result in significant maternal- neonatalcomplications.